Complementary and Alternative Medicine Use Among Women During Pregnancy and Childbearing Years. Issue 2 (February 2016) - Holden, Selma C.; Gardiner, Paula; Birdee, Gurjeet; Davis, Roger B.; Yeh, Gloria Y.
Abstract : Obstet Gynecol Surv 2016;71(2):57–58 In response to a high rate of unplanned pregnancies, public health initiatives have focused on the importance of preconception health counseling for women of childbearing age who may become pregnant, either intentionally or unintentionally. Nearly half of women in this age group have used some type of complementary and alternative medicine (CAM).